Serum concentration of extracellular cold-inducible RNA-binding protein is associated with respiratory failure in COVID-19 - Schagatay, Felix; Diamant, Klara; Lidén, Mats; Edin, Alicia; Athlin, Simon; Hultgren, Olof; Ahlm, Clas; Forsell, Mattias N. E.; Savilampi, Johanna; Normark, Johan; Lange, Anna; Cajander, Sara (Frontiers in Immunology, 2022)
Uncontrolled release of damage-associated molecular patterns (DAMPs) is suggested to be a major trigger for the dysregulated host immune response that leads to severe COVID-19. Cold-inducible RNA-binding protein (CIRP), is a newly identified DAMP that aggravates inflammation and tissue injury, and induces respiratory failure in sepsis. Whether CIRP contributes to the pathogenesis of respiratory failure in COVID-19 has not yet been explored. Aim To investigate if the concentration of extracellular CIRP (eCIRP) in serum associates with respiratory failure and lung involvement by chest computed tomography (CT) in COVID-19. Methods Herein we report a prospective observational study of patients with COVID-19 included at two University Hospitals in Sweden between April 2020 and May 2021. Serum from hospitalized patients in Örebro (N=97) were used to assess the association between eCIRP and the level of respiratory support and its correlation with pulmonary involvement on chest CT and inflammatory biomarkers. A cohort of hospitalized and non-hospitalized patients from Umeå (N=78) was used as an external validation cohort. The severity of disease was defined according to the highest degree of respiratory support; mild disease (no oxygen), non-severe hypoxemia (conventional oxygen or high-flow nasal oxygen, HFNO <50% FiO2), and severe hypoxemia (HFNO ≥50% FiO2, mechanical ventilation). Unadjusted and adjusted linear regression was used to evaluate peak eCIRP day 0-4 in respect to severity, age, sex, Charlson comorbidity score, symptom duration, and BMI. Results Peak eCIRP concentrations were higher in patients with severe hypoxemia and were independently associated with the degree of respiratory support in both cohorts (Örebro; p=0.01, Umeå; p<0.01). The degree of pulmonary involvement measured by CT correlated with eCIRP, rs=0.30, p<0.01 (n=97). Conclusion High serum levels of eCIRP are associated with acute respiratory failure in COVID-19. Experimental studies are needed to determine if treatments targeting eCIRP reduces the risk of acute respiratory failure in COVID-19.